1987
DOI: 10.1143/jjap.26.1555
|View full text |Cite
|
Sign up to set email alerts
|

Plasma CVD of Amorphous AlN from Metalorganic Al Source and Properties of the Deposited Films

Abstract: AlN films have been successfully deposited by plasma CVD for the first time. Al was supplied by trimethyl Al (TMA) with H2 or N2 carrier gas, and N was supplied as NH3 through separate gas lines. The deposition rate depends upon the TMA supply, and is essentially independent of the NH3 flow rate. The composition of the deposited films was almost AlN, although a small amount of oxygen was always detected. A better film was obtained for the H2 carrier gas than for N2 carrier gas. X-ray diffraction profiles of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(38 citation statements)
references
References 7 publications
3
35
0
Order By: Relevance
“…Using an analogous etching procedure, results comparable with the present ones were obtained by Hagesawa et al [9] for their AIN films prepared from Al(CH3)3 and NH3 by plasma CVD at 300 "C. On the other hand, Gordon et al [l01 reported that their AlN films prepared from &@(CH3)&, and NH3 by atmospheric CVD in a temperature range 100 -500 "C were dissolved with an approximate rate of 100 nm min-l under identical etching conditions.…”
Section: Film Structure Composition and Propertiessupporting
confidence: 92%
“…Using an analogous etching procedure, results comparable with the present ones were obtained by Hagesawa et al [9] for their AIN films prepared from Al(CH3)3 and NH3 by plasma CVD at 300 "C. On the other hand, Gordon et al [l01 reported that their AlN films prepared from &@(CH3)&, and NH3 by atmospheric CVD in a temperature range 100 -500 "C were dissolved with an approximate rate of 100 nm min-l under identical etching conditions.…”
Section: Film Structure Composition and Propertiessupporting
confidence: 92%
“…Similar behavior has been demonstrated for sputtered and CVD AlN. 35,36 The change in the oxygen content likely reflects also on the density changes of the samples; the 1:1 flow samples have larger changes in the density. The effects on the refractive index are not as pronounced in either of the sample types and the total changes are in the range of a couple percent.…”
Section: B Composition and Structuresupporting
confidence: 67%
“…Figure 2 shows the typical IR absorption spectrum of gas phase DMEAA in the cell. The peaks of Al-N (768 cm Ϫ1 ) 18,19 and Al-H (1793 cm Ϫ1 ) 20 are clearly seen in Fig. 2 and several peaks from DMEA are also shown.…”
Section: Methodsmentioning
confidence: 85%